ORGANIZATION OF ARCHITECTURAL ENVIRONMENT OF TOURIST ROUTE OBJECTS OF SURKHANDARYA REGION (Intent Research Scientific Journal, 2023)
In this research, the authors aim to analyze the architectural environment of these tourist route objects and propose recommendations for their effective organization. The study investigates the current state of the architectural environment, the layout of objects, infrastructure, and accessibility. The findings of this study highlight the importance of a well-designed architectural environment in attracting tourists and enhancing their overall experience. Several recommendations are proposed, including improving the infrastructure, optimizing the layout of objects, enhancing accessibility, and emphasizing the cultural and historical significance of the region. Overall, this research provides valuable insights into improving the organization of tourist route objects in the Surkhandarya region, with the goal of promoting tourism and enhancing the overall visitor experience.